Tactile acuity is reduced in people with chronic neck pain. (February 2018) - Harvie, Daniel S.; Edmond-Hank, Grace; Smith, Ashley D.
Abstract: Background: Tactile acuity deficits have been demonstrated in a range of persistent pain conditions and may reflect underlying cortical re-organisation. Objective: This study aimed to determine whether tactile acuity is impaired in people with chronic neck pain relative to controls, and whether deficits relate to pain location, duration and intensity. Methods: In this cross-sectional study, 20 people with chronic neck pain (5 idiopathic neck pain; 15 whiplash-associated disorder) and 20 pain-free controls underwent two-point discrimination (TPD) testing at the neck, back and arm, and point-to-point (PTP) and graphesthesia tests of tactile acuity at the neck and arm. Results: Linear mixed effects models demonstrated a significant group*body region interaction for TPD, Graphesthesia and PTP tests ( Ps < 0.001), with post hoc tests showing impaired TPD in people with neck pain relative to controls at the neck, low back, and arm ( P ≤ 0.001). Graphesthesia and PTP was also impaired at the neck ( P < 0.001) but not the arm ( P ≥ 0.48). TPD correlated with intensity and duration of pain (Pearson's r = 0.48, P < 0.05; Pearson's r = 0.77, P < 0.01). There was no sig difference between the two neck pain groups for any tactile acuity measure (TPD: P = 0.054; Graphesthesia; P = 0.67; Point to Point: P = 0.77), however, low power limited confidence in this comparison. Conclusion: People with chronic neck pain demonstrated tactile acuity deficits in painful and non-painful regions when measured using the TPD test, with the magnitude of deficits appearing greatest at the neck. The study also revealed a positive relationship between TPD and pain intensity/duration, further supporting the main study finding. Highlights: People with chronic neck pain show reduced tactile acuity. Tactile acuity deficits are greatest at, but not localised to, the neck. Tactile acuity deficits correlate with pain intensity and duration.